Analysis of investment in Sarolangun Regency - Siti Aminah (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
This study aims to analyze the condition and the development of investment, especially invesment in oil palm plantation and coal mining in Sarolangun Regency. The results found that 1) Based on the ownership of capital, investment realization in Sarolangun Regency in oil palm plantation and coal mine is still dominated by domestic investment, referred as PMDN; 2) Based on the stages of activity, investment in oil palm plantation is dominated by operational stage, while in coal mining is dominated by exploration stage; 3) In terms of invesment realization, investment in oil palm plantation sector decreased while in coal mining sector increased every year. Keywords: Investment, Palm plantation, Coal Minning